Competitiveness in Industrial Distribution: A Case Study - Lee, Adrian Eng Lye (2008)
The industrial distributor plays an important intermediary role in the supply chain through its relationships with suppliers and customers. Increased globalisation and competitiveness have however resulted in the diminishing role of the distributor. A common source of worry for many small and medium enterprises (SME) is the plaguing of stiff competitions from rival firms in the distribution industry. This dissertation evaluates the factors that impact on the competitiveness of a SME chemical distributor using Porter’s Five Forces analytical framework. The framework will be used to obtain an understanding of the firm’s strengths in its current competitive position and hence provide recommendations for the necessary steps to be taken by the firm in enhancing its competitive advantage.